2018
DOI: 10.1002/mrm.27636
|View full text |Cite
|
Sign up to set email alerts
|

Non‐contrast myocardial infarct scar assessment using a hybrid native T1 and magnetization transfer imaging sequence at 1.5T

Abstract: Purpose To develop a gadolinium‐free cardiac MR technique that simultaneously exploits native T1 and magnetization transfer (MT) contrast for the imaging of myocardial infarction. Methods A novel hybrid T one and magnetization transfer (HYTOM) method was developed based on the modified look‐locker inversion recovery (MOLLI) sequence, with a train of MT‐prep pulses placed before the balanced SSFP (bSSFP) readout pulses. Numerical simulations, based on Bloch‐McConnell equations, were performed to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
(126 reference statements)
1
5
0
Order By: Relevance
“…Our results did not show evidence of an increase of the bound pool in the presence of replacement fibrosis/collagen, that is, in the chronic MI patients. On the contrary, a reduction of the MT effects was observed, which is consistent with findings in chronic myocardial infarction in rats by Scholz et al, 35 findings of fibrosis in end‐stage renal disease (ESRD) patients by Stromp et al, 36 and reports from Duan et al 13 in 15‐mo (average) post MI patients using a hybrid T1/MT –weighted sequence. The proposed sequence may present advantages over Duan et al and Stromp et al in terms of quantification of the bound pool and potential specificity to fibrosis, since the cited approaches rely on combining the MT contrast with T1 and/or T2 weighting.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results did not show evidence of an increase of the bound pool in the presence of replacement fibrosis/collagen, that is, in the chronic MI patients. On the contrary, a reduction of the MT effects was observed, which is consistent with findings in chronic myocardial infarction in rats by Scholz et al, 35 findings of fibrosis in end‐stage renal disease (ESRD) patients by Stromp et al, 36 and reports from Duan et al 13 in 15‐mo (average) post MI patients using a hybrid T1/MT –weighted sequence. The proposed sequence may present advantages over Duan et al and Stromp et al in terms of quantification of the bound pool and potential specificity to fibrosis, since the cited approaches rely on combining the MT contrast with T1 and/or T2 weighting.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have explored the use of MT ratio (MTR) for gadolinium‐free assessment of chronic or acute myocardial fibrosis. In vivo studies have shown reductions of the MT effects associated with both acute 11,12 and over 10‐mo old myocardial infarction (MI) 13 . A post‐mortem study 9 found correlation between increased MTR and fibrous tissue in histology, while some areas of decreased MTR were associated with inflammatory granulocyte infiltration at a microscopic level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical significance of gadolinium deposition remains to be determined [152]. Nevertheless, novel techniques that allow quantitative characterization of the infarcted and non-infarcted myocardium after myocardial infarction without the need of a gadolinium contrast agent have been investigated recently [97,[153][154][155][156][157]. CMR infarct characterization and prognostication without using contrast agents is an interesting concept, but the prognostic role of non-contrast CMR compared to contrast-enhanced CMR remains to be defined.…”
Section: Remaining Challenges and Opportunitiesmentioning
confidence: 99%
“…Interestingly, MOLLI T 1 mapping, which is most common in clinical use, is known to exhibit a large bias. However, it has been suggested that certain confounders to MOLLI T 1 measurements may enhance clinical sensitivity 137 . As illustrated in Figure 7, this somewhat counter‐intuitive phenomenon arises because some confounders (e.g., magnetization transfer 84,137,138 ) are sensitive to pathological alterations, leading to inflated effect size in certain disease entities compared to unbiased measurements.…”
Section: Clinical Qualificationmentioning
confidence: 99%